Understanding Plant Diversity from Ecological and Evolutionary Perspectives - Hong-Hu Meng; Yi-Gang Song (Diversity, 2023)
Nowadays, we are living in a world that is benefiting from biodiversity, although environmental change is dramatic and biodiversity has been influenced by climate changes and human activities [...]